Mycophenolate Mofetil after Rituximab for Childhood-Onset Complicated Frequently-Relapsing or Steroid-Dependent Nephrotic Syndrome. Issue 2 (February 2022) - Iijima, Kazumoto; Sako, Mayumi; Oba, Mari; Tanaka, Seiji; Hamada, Riku; Sakai, Tomoyuki; Ohwada, Yoko; Ninchoji, Takeshi; Yamamura, Tomohiko; Machida, Hiroyuki; Shima, Yuko; Tanaka, Ryojiro; et al.
Significance Statement: Rituximab is the standard therapy for childhood-onset complicated frequently relapsing or steroid-dependent nephrotic syndrome (FRNS/SDNS). However, most patients redevelop FRNS/SDNS after peripheral B cell recovery. This multicenter, randomized, double-blind, placebo-controlled trial was conducted to examine whether mycophenolate mofetil (MMF) administration after rituximab can prevent treatment failure (FRNS, SDNS, steroid resistance, or use of immunosuppressive agents or rituximab) in these patients. MMF after rituximab decreased the risk of treatment failure during the MMF administration period by 80% and was well tolerated. However, after MMF discontinuation, the relapse-preventing effect disappeared, and most patients in the MMF group presented with treatment failure. In conclusion, MMF maintenance therapy after rituximab may be an option for sustaining remission in children with complicated FRNS/SDNS. Visual Abstract: Abstract : Background: Rituximab is the standard therapy for childhood-onset complicated frequently relapsing or steroid-dependent nephrotic syndrome (FRNS/SDNS). However, most patients redevelop FRNS/SDNS after peripheral B cell recovery. Methods: We conducted a multicenter, randomized, double-blind, placebo-controlled trial to examine whether mycophenolate mofetil (MMF) administration after rituximab can prevent treatment failure (FRNS, SDNS, steroid resistance, or use of immunosuppressive agents or rituximab). In total, 39 patients (per group) were treated with rituximab, followed by either MMF or placebo until day 505 (treatment period). The primary outcome was time to treatment failure (TTF) throughout the treatment and follow-up periods (until day 505 for the last enrolled patient). Results: TTFs were clinically but not statistically significantly longer among patients given MMF after rituximab than among patients receiving rituximab monotherapy (median, 784.0 versus 472.5 days, hazard ratio [HR], 0.59; 95% confidence interval [95% CI], 0.34 to 1.05, log-rank test: P =0.07). Because most patients in the MMF group presented with treatment failure after MMF discontinuation, we performed a post-hoc analysis limited to the treatment period and found that MMF after rituximab prolonged the TTF and decreased the risk of treatment failure by 80% (HR, 0.20; 95% CI, 0.08 to 0.50). Moreover, MMF after rituximab reduced the relapse rate and daily steroid dose during the treatment period by 74% and 57%, respectively. The frequency and severity of adverse events were similar in both groups. Conclusions: Administration of MMF after rituximab may sufficiently prevent the development of treatment failure and is well tolerated, although the relapse-preventing effect disappears after MMF discontinuation.